Kinerja DPRD Kota Yogyakarta: Studi Pembentukan Peraturan Daerah Prakarsa DPRD 2019-2020 - Muhammad Rizky Saputra; Anom Wahyu Asmorojati (Universitas Batanghari Jambi, 2021)
Implementation the formulation of Regional Regulation by the Yogyakarta Legislative Council was not optimum, especially regarding the performance in proposing the draft bylaws. It was evidenced by the number of drafts from 2019-2020 from the Initiatives of Yogyakarta Legislative Council, which were only 4 draft bylaws, a quite low number compared to the executive which proposed 15 draft bylaws. Furthermore, the factors affecting the performances of the members of the Yogyakarta Legislative council in carrying out its function to formulate the regional regulations were the lack of experiment in organizations, different and limited backgrounds of education, and the lack of people’s enthusiasm to participate in the formulation of Regional Regulations. This study aims to analyze the implementation of the legislative functions of The Yogyakarta Legislative Council in the formulation of Regional Regulation Initiatives based on the Regulation of the Yogyakarta Legislative Council Number 1 Year 2018 on Code of Conduct and to find out the factors affecting the performance of the members of the Yogyakarta Legislative Council in implementing their functions in the formulations of regional regulations. This study employed an the normative legal and empirical legal method